Experimental Research on End Joint of Steel-Concrete Composite Truss - Lingyu Zhou; Guichao He (The Baltic Journal of Road and Bridge Engineering)
Steel-concrete composite truss is characterized by such advantages: high stiffness, low height and construction costs. Moreover, it has promising application prospects. Since the interfacial load between concrete and steel is still indeterminate, experimental research and finite element analysis were carried out on two samples in scale of 1:3 models of composite truss joint models. A detailed account of the design philosophy, structural origin, loading procedure and test items followed. Test results showed that under design load, the joints were at elastic stage all along. Joints cracking load was twice as much as the design load. Their yield load was 3.2 times the design load and the ultimate load was 3.5 times the design load. The joints had a high safety factor which met the design requirements. The joints failing process was that cracks appeared on concrete first, and the web members yielded soon after, leading to joint yield. Now that both the concrete chord and the steel web members failed, there is no obvious increase in joint bearing capacity after joint yield. But the joints underwent severe deformation and possessed good ductility. For this reason, the joints could be applied in engineering practice.